The influence of aluminum and oxygen additions on intrinsic structural instabilities in titanium-molybdenum alloys. (15th July 2018) - Zheng, Yufeng; Alam, Talukder; Banerjee, Rajarshi; Banerjee, Dipankar; Fraser, Hamish L.
Abstract: The influences of aluminum and oxygen additions on structural instabilities in the β phase of binary Ti‐Mo alloys have been investigated, using conventional and aberration-corrected scanning/transmission electron microscopy and atom-probe tomography. An addition of 5 wt% Al to the alloy Ti-18 wt% Mo tends to decrease the stability of the 2/3<111> longitudinal phonon, compared with that of the phase O′ formed by the 110 < 1 1 ¯ 0 > transverse phonon. Experiments have been performed to assess whether interstitial oxygen influences these phase instabilities by adding yttrium to getter the matrix oxygen. It has been found that oxygen is not a necessary alloying addition to form the O′ phase. Graphical abstract: Unlabelled Image